2017
DOI: 10.1017/s0022215117002377
|View full text |Cite
|
Sign up to set email alerts
|

New generation cut-and-seal devices in oral and oropharyngeal cancer resection: clinical and cost-effectiveness study

Abstract: Ultrasonic shears and, in particular, electrothermal bipolar vessel sealing, are more advantageous compared to the traditional techniques, from both a clinical and economic point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As for neck LND, Chen et al 11 published a systematic review and meta‐analysis, which included four studies (one prospective randomized trial, three retrospective studies) 21–24 which investigated the efficacy of LigaSure™ for head and neck cancer. The meta‐analysis concluded that the use of LigaSure™ shortens operating time compared use of conventional techniques in neck LND; however, LigaSure™ did not positively affect intraoperative blood loss, time to drain removal, duration of hospital stay, and postoperative bleeding and infection.…”
Section: Discussionmentioning
confidence: 99%
“…As for neck LND, Chen et al 11 published a systematic review and meta‐analysis, which included four studies (one prospective randomized trial, three retrospective studies) 21–24 which investigated the efficacy of LigaSure™ for head and neck cancer. The meta‐analysis concluded that the use of LigaSure™ shortens operating time compared use of conventional techniques in neck LND; however, LigaSure™ did not positively affect intraoperative blood loss, time to drain removal, duration of hospital stay, and postoperative bleeding and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding is a potential peri‐ and postoperative complication of palatal harvesting, and a bipolar coagulator is useful in achieving hemostasis during surgery. The effects of using a bipolar coagulator in palatal harvesting procedures have never been described, although this particular instrument is widely used in other surgical fields (Advincula & Wang, 2008 ; Cannizzaro et al, 2016 ; Janssen et al, 2012 ; Tirelli et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%